Pengaruh Tingkat Suku Bunga The Fed dan Suku Bunga Bank Indonesia Terhadap Portfolio Investment Di Indonesia - Yudhoyono, Andika Dwi; Yudha, I Made Endra Kartika (Jurnal Ilmiah Wahana Pendidikan, 2024)
The era of globalization has caused an increase in the flow of capital between countries, particularly from developed nations to developing ones. Capital flow in a country's economy refers to the movement of financial capital (such as money, investments, and financial assets) between countries. In theory, fluctuations in this capital flow are influenced by numerous factors, which are generally classified as push factors (external factors) and pull factors (internal factors). One of these factors is the interest rate, which affects the decision to invest in a country. Interest rates play a crucial role in attracting capital flow in the form of portfolio investments to a country, including Indonesia. The focus of this study then examines the influence of the interest rates set by The Fed and Bank Indonesia on the flow of portfolio investments in Indonesia during the period between 2011 and 2022. By utilizing multiple linear regression modeling, this research demonstrates that Bank Indonesia's interest rate partially has a positive impact on the fluctuations of portfolio investments in Indonesia, while The Fed's interest rate does not have a significant effect. Moreover, both independent variables simultaneously have a significant impact on changes in portfolio investments. These findings align with the descriptive analysis in this study regarding the monetary policy conducted by Bank Indonesia as the dominant influencing factor, as well as the investment climate in Indonesia which is considered relatively robust against the influence of external factors.